Corruption in Peru: situation, responses, and results - Martínez Huamán, Raúl Ernesto (2023)
The author, based on statistical data, observes the increase of corruption crime reports. Based on that, he analyzes the existing repressive criminal policies to fight against said crime, such as sentencing increase or new corruption crime types. However, when observing the rate of imprisonments, it can be seen that the number of people convicted to prison due to corruption cases has not increased; one of the reasons would be linked to sentence conversion, despite the fact that Section 57 of the Criminal Code establishes its effectiveness.